2005
DOI: 10.1021/cm048796e
|View full text |Cite
|
Sign up to set email alerts
|

Isovalent Doping Strategy for Manganese Introduction into III-V Diluted Magnetic Semiconductor Nanoparticles:  InP:Mn

Abstract: III-V based diluted magnetic semiconductor (DMS) nanoparticles of In (1-x) Mn x P (x e 0.0135) have been prepared by slow heating of the reagents in trioctylphosphine oxide (TOPO) or by high-temperature injection of reagents dissolved in trioctylphosphine (TOP) into hot TOPO. The materials were prepared using either Mn(II) or Mn(III) salts as dopants and the resulting nanoparticles have diameters ranging from 2.95 ( 0.39 to 4.77 ( 0.73 nm, as determined from transmission electron micrographs. Chemical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 49 publications
0
29
0
1
Order By: Relevance
“…However, a significant amount of dopants will be incorporated in "bulklike" sites, especially for thicker wires in agreement with the experimental results. 22 In Fig. 3 we show some relevant majority-spin energy levels with d character for the different dopant positions.…”
Section: Resultsmentioning
confidence: 99%
“…However, a significant amount of dopants will be incorporated in "bulklike" sites, especially for thicker wires in agreement with the experimental results. 22 In Fig. 3 we show some relevant majority-spin energy levels with d character for the different dopant positions.…”
Section: Resultsmentioning
confidence: 99%
“…The covalent nature of the different Mn 2+ sites can be revealed via hyperfine splitting, allowing Mn 2+ ions located within the nanocrystal lattice (on substitutional positions) to be distinguished from Mn 2+ coordinated within other compounds or at other types of site . Accordingly, Mn 2+ ions at surface ionic sites or sites with significant lattice distortion should show much larger hyperfine splitting than Mn 2+ ions on internal sites within ordered lattices . Mn 2+ ions substituted for Zn 2+ and Cd 2+ on covalently bound tetrahedral sites in cubic bulk ZnS and CdTe lattices typically show hyperfine splitting constants of 64 × 10 −4 cm −1 and 57 × 10 −4 cm −1 respectively.…”
Section: Heterocrystalline Growthmentioning
confidence: 99%
“…Much larger values of around 90 × 10 −4 cm −1 , consistent with a predominantly octahedral environment, have been identified with either interstitial or surface lattice bound Mn 2+ locations . For Mn‐doped CdSe QDs, and InP QDs, hyperfine splitting constants of 83 × 10 −4 cm −1 and 82.5–87.6 × 10 −4 cm −1 respectively have been observed, though it has also been shown that more complex core@shell structures such as CdSe@ZnS:Mn, CdTe@ZnS:Mn can substantially influence the splitting constant values . In terms of deciding upon the best doping structure, it is helpful to know that Mn 2+ ions have high binding energies at the zinc blende (001) facets of II–VI nanocrystals .…”
Section: Heterocrystalline Growthmentioning
confidence: 99%
“…QYs of about 15% were obtained prior to etching and improved to 68% upon etching due to the passivation of surface states. Few literature reports on the doping of InP QDs are due to the low solubility of the dopants in the III-V semiconductor matrix [57,58]. Manganese-doped InP QDs were obtained by using the hightemperature dehalodesilylation and injection methods in a coordinating solvent.…”
Section: Alloying and Doping Of The Inp Qdsmentioning
confidence: 99%